The long‐term impact of cancer: Evaluating psychological distress in adolescent and young adult cancer survivors in Switzerland. Issue 3 (24th January 2019) - Michel, Gisela; François, Constanza; Harju, Erika; Dehler, Silvia; Roser, Katharina
Abstract: Objectives: Adolescents and young adults (AYAs) are diagnosed with cancer during a critical life period full of psychosocial challenges. They may experience a significant impact of the cancer diagnosis on their psychological health, also in the long term. We aimed to (a) evaluate psychological distress in AYA cancer survivors and compare levels of distress with controls and (b) describe socio‐demographic and cancer‐related characteristics associated with psychological distress. Methods: We sent a questionnaire to AYA cancer survivors (aged 16‐25 y at diagnosis, survived ≥5 y) registered in the Cancer Registry Zurich and Zug, Switzerland. Psychological distress was measured using the Brief Symptom Inventory‐18 (BSI‐18) assessing anxiety, depression, and somatization and a global severity index (GSI) (cutoff score indicating psychological distress: T ≥ 57). Distress levels were compared between survivors and controls. We used logistic regression to determine associations of socio‐demographic and cancer‐related characteristics with distress. Results: Of 160 AYA cancer survivors, 34 (21%) reported being distressed (27% in women, 17% in men; P = 0.129). Compared with controls, survivors did not report higher levels of distress (all P values > 0.05). Survivors with migration background and survivors with late effects reported higher levels on GSI, somatization, and anxiety. Higher levels of depression were associated with being female, not being in a partnership, and having late effects. Conclusions: A substantial subgroup of AYA cancer survivors reported psychological distress. Systematically screening for distress and providing psychological follow‐up for survivors at risk may help to provide adequate psychological support.